Genetic Analyses of the rbcL and psaA Genes From Single Cells Demonstrate a Rhodophyte Origin of the Prey in the Toxic Benthic Dinoflagellate Ostreopsis - Lee, Bora; Park, Myung G. (Frontiers in Marine Science, 2018)
Phagotrophy of the harmful benthic dinoflagellates of the genus Ostreopsis has long been inferred based on observations of food particles present inside cells, but the prey has not yet been identified. This study aimed to investigate the seasonal dynamics of benthic dinoflagellates Ostreopsis spp. in temperate Korean coastal sites, with special emphasis on their phagotrophy. Further, prey species were identified by extracting the ingested food particles from single Ostreopsis cells and determining their rbcL and psaA gene sequences. High concentration of Ostreopsis cells was observed between June and October at all sites, when the water temperatures were higher than 19°C, exhibiting a marked temporal seasonality. The percentage of Ostreopsis cells containing ingested food particles exhibited large spatial and temporal variations among sampling sites, ranging from undetectable level to 29.5%, and was not always associated with Ostreopsis cell abundance. Phylogenetic analyses performed using both plastid-encoded rbcL and psaA genes revealed that all sequences obtained from the ingested food particles of Ostreopsis cells grouped within the class Florideophyceae, Rhodophyta. Our result clearly demonstrates that Ostreopsis species consume various macroalgae from Rhodophyta, but not protists, which have long been thought to be the potential prey. The results of this study provide a basis for better understanding the mixotrophic behavior and nutritional ecology of the harmful benthic dinoflagellate Ostreopsis species.